PENINGKATAN KETERAMPILAN MANAJEMEN DIRI SISWA SMP MELALUI PELATIHAN PENGGUNAAN GOOGLE CALENDAR - Alfa Santoso Budiwidjojo Putra; Poernomo, Moyo Hady; Dwiyani, Titik; Aescoulafianto, Renata Ellena (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This community service program aims to enhance the self-management skills of students at SMP Kanisius Muntilan through training in the use of Google Calendar. The background of the issue highlights that students often face challenges in balancing academic activities, extracurricular engagements, and rest time. Limited access to additional educational programs outside of school further exacerbates this condition. This training is designed to provide an understanding of the importance of time management as well as practical skills in creating daily schedules, setting priorities, and managing stress. The implementation method involves a series of activities, including program socialization, intensive training on Google Calendar features and utilization, direct application of technology in schedule planning, as well as regular mentoring and evaluation to ensure effective understanding and application. The training results indicate a significant improvement in students' self-management skills. Students reported increased abilities in managing their time, setting task priorities, and utilizing Google Calendar features to enhance learning efficiency. Additionally, the program has had a positive impact on students' mental well-being, with many feeling more capable of managing stress and academic pressure. These findings emphasize the importance of integrating technology into education as a tool to help students develop skills relevant to modern demands. This program is expected to serve as a model for other schools in their efforts to empower youth and improve educational quality through the optimal use of technology.